Small apolipoprotein(a) isoforms may predict primary patency following peripheral arterial revascularization - Marianna Pavlyha, MD; Madeleine Hunter, MD; Roman Nowygrod, MD; Virenda Patel, MD, MPH; Nicholas Morrissey, MD; Danielle Bajakian, MD; Yihao Li, MS; Gissette Reyes-Soffer, MD (JVS - Vascular Science)
Background: High lipoprotein (a) [Lp(a)] is associated with adverse limb events in patients undergoing lower extremity revascularization. Lp(a) levels are genetically pre-determined, with LPA gene encoding for two apolipoprotein (a) [apo(a)] isoforms. Isoform size variations are driven by the number of kringle IV type 2 (KIV-2) repeats. Lp(a) levels are inversely correlated with isoform size. In this study, we examined the role of Lp(a) levels, apo(a) size, and inflammatory markers with lower extremity revascularization outcomes. Methods: Twenty-five subjects with chronic peripheral arterial disease (PAD) underwent open or endovascular lower extremity revascularization (mean age, 66.7 ± 9.7 years; Female = 12; Male = 13; Black = 8; Hispanic = 5; and White = 12). Pre- and postoperative medical history, self-reported symptoms, ankle-brachial indices (ABIs), and lower extremity duplex ultrasounds were obtained. Plasma Lp(a), apoB100, lipid panel, and pro-inflammatory markers (IL-6, IL-18, hs-CRP, TNFα) were assayed preoperatively. Isoform size was estimated using gel electrophoresis and weighted isoform size (wIS) calculated based on % isoform expression. Firth logistic regression was used to examine the relationship between Lp(a) levels and wIS with procedural outcomes: symptoms (better/worse), early primary patency at 2 to 4 weeks, ABIs, and reintervention within 3 to 6 months. We controlled for age, sex, history of diabetes, smoking, statin, antiplatelet, and anticoagulation use. Results: Median plasma Lp(a) level was 108 (interrquartile range, 44-301) nmol/L. The mean apoB100 level was 168.0 ± 65.8 mg/dL. These values were not statistically different among races. We found no association between Lp(a) levels and wIS with measured plasma pro-inflammatory markers. However, smaller apo(a) wIS was associated with occlusion of the treated lesion(s) in the postoperative period (odds ratio, 1.97; 95% confidence interval, 1.01-3.86; P < .05). The relationship of smaller apo(a) wIS with reintervention was not as strong (odds ratio, 1.57; 95% confidence interval, 0.96-2.56; P = .07). We observed no association between wIS with patient reported symptoms or change in ABIs. Conclusions: In this small study, subjects with smaller apo(a) isoform size undergoing peripheral arterial revascularization were more likely to experience occlusion in the postoperative period and/or require reintervention. Larger cohort studies identifying the mechanism and validating these preliminary data are needed to improve understanding of long-term peripheral vascular outcomes.